ChemInform Abstract: Review: Bismuth Complexes: Synthesis and Applications in Biomedicine. Issue 12 (March 2015) - Yang, Yang; Ouyang, Ruizhuo; Xu, Lina; Guo, Ning; Li, Weiwei; Feng, Kai; Ouyang, Lei; Yang, Zhuoyuan; Zhou, Shuang; Miao, Yuqing
Abstract Review: 85 refs.